The Bahraini Daily Press Coverage of Women Issues): (Analytical Study - بني دومي محمد خير (ALBAHITH ALALAMI, 2017)
This research is an attempt to assess the extent of coverage given by the Bahrain daily press to Women and related issues. It attempts to determine how important the issues of the Women issues were covered in the Daily Press and whether the press has given enough attention to the Women issues. The research was conducted by analyzing the coverage “AkhbarAlKhaleej” Daily newspaper gave the Women issues during the period of this study. Thus, this study aims at assessing the degree to which the Bahraini daily newspapers have dealt with the Women issues. The researcher analyzed the contents of the Bahraini press, “AKHBAR ALKHALEEJ” daily newspaper during 2014, as Bahraini press coverage seems to be stable, and more balanced and not influenced by current events. In regard to the Bahraini daily press coverage of the Women issues, the topic of the study, as pointed out in the title, has raised a number of questions. First, what were the main issues that attracted the Bahraini daily press coverage towards the Women issues? Second, How important the issues of the Women issues were covered in the Daily Press?The study concluded that:The highest percentage (22.1%) was given to the coverage that was devoted to Cultural and Education issues. Second highest percentage (21.4%) was given to coverage that wasdevoted to Violence issues.However, lowest percentage (10.7%) was given to coverage that was devoted to Laws and regulations related to Women. The Bahraini press devoted a greater amount of its coverage to Women topics; (54.8%) of its related coverage appeared combined with photos. (35.5%) of its related coverage appeared in the headlines of its pages.